Spinal cord findings in a long-term survivor of Duchenne muscular dystrophy - Ruruka Imaizumi; Tomoko Yamamoto; Kenta Masui; Keiko Ishigaki; Takatoshi Sato; Terumi Murakami; Minobu Shichiji; Kumiko Ishiguro; Atsushi Kurata (Elsevier, 2024)
Duchenne muscular dystrophy (DMD) is the most common type of muscular dystrophy, but the spinal cord is rarely examined. Here we report a case of DMD with interesting spinal cord findings. In a 37-year-old man with DMD accompanied by hypoxic encephalopathy from the age of 32 years, autopsy showed amyotrophic lateral sclerosis-like pyramidal tract degeneration over the entire spinal cord, presumably due to hypoxic encephalopathy. Furthermore, anterior horn cells exhibited Wallerian degeneration-like changes. To investigate more about the pathogenesis, an immunohistochemical study using anti-synaptophysin, glutamic acid decarboxylase (GAD), postsynaptic density protein-95 (PSD-95) and choline acetyltransferase (ChAT) antibodies was performed. Immunostaining for synaptophysin showed that the number of synapses around anterior horn cell were decreased, contrary to the finding of teenage DMD, in which the number of synapses were increased, probably due to the reaction toward the reduced anterior horn cell activity. The decrease of synapses of the present case may be mainly due to hypoxic encephalopathy, based on the degeneration of the pyramidal tract. Another interesting finding is that GAD was strongly positive in the cytoplasm of anterior horn cells, which may be explained by Wallerian degeneration-like mechanism. Moreover, the expression of PSD-95 is increased in anterior horn cells. Compensation for postsynaptic damage can be considered, since dystrophin is necessary for maintaining the post-synaptic maintenance. There were no apparent differences in ChAT immunostaining. Further investigation is necessary whether these findings are characteristic of long-term surviving cases accompanied by hypoxic encephalopathy.